Syntheses and Antibacterial Studies of Some 1-Phenyl-3-(4-(2-ethanoloxy) phenyl)-5-aryl-1H-pyrazoles - Anju Goyal; Sandeep Jain (Journal of Chemistry)
A series of 1-phenyl-3-(4-(2-ethanoloxy) phenyl)-5-aryl-1H-pyrazoles were synthesized from chalcones, that is, 3-aryl-1-(4-hydroxyphenyl) prop-2-en-1-ones and studied for their in vitro antibacterial activity. Chalcones 1 on reaction with phenyl hydrazine in the presence of acetic acid and few drops of hydrochloric acid yielded the corresponding 1-phenyl-3-(4-hydroxyphenyl)-5-aryl-1H-pyrazoles 2 which on further reaction with 2-chloroethanol furnished the title compounds 3. These compounds were characterized by CHN analyses, IR, mass and 1H NMR spectral data. All the compounds were evaluated for their in vitro antibacterial activity against two Gram positive strains (Bacillus subtilis and Staphylococcus aureus) and two Gram negative strains (Escherichia coli and Pseudomonas aeruginosa), and their minimum inhibitory concentration (MIC) was determined.